(untitled) (Journal of Dhaka Medical College, 2015)
Background: Glomerular filtration rate (GFR) reflects renal function and in chronic kidney disease (CKD) stage 3-5, there is electrolyte imbalance which is reflected by changes in serum creatinine and phosphate level. The aim of this study was to determine GFR in advanced stages of CKD and its relation with serum creatinine and serum inorganic phosphate. Methods: This was a cross sectional study which was done in Rajshahi Medical College, Rajshahi. A total of 120 patients were taken. Among them ninety were with advanced stages of CKD and thirty were as control group. Results: Mean GFR in healthy control was 104.953±16.663 ml/min., mean GFR in CKD3 group was 36.256±5.582, in CKD4 group was 21.142±5.420 ml/min. and in CKD5 group was 10.304±2.694 ml/min. Mean serum creatinine in healthy control was 0.936±0.116 mg/dl and 2.226±0.272, 3.698±0.915 & 6.906±2.439 mg/dl in CKD3, CKD4 & CKD5 respectively. While, the mean serum inorganic phosphate level in healthy control group was 1.23±0.17 mmol/L, and 1.79±0.11, 2.09±0.27 & 3.04±0.33 mmol/L in CKD3, CKD4 & CKD5 respectively. Conclusion: Serum creatinine and phosphate levels are increased with the severity of CKD. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22692 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 37-40